Gen Z Attitude and Its Factors towards Social Media Advertisements - Nartea, Mecmack (Social Sciences and Development Review, 2024)
With the radical growth of technology and the Internet of Things, social media sites rose as an essential tool in promoting products and services. The intergenerational cohorts are also rapidly growing in the e-business limelight. Various studies targeted millennial consumers and less on Gen Z. Thus, this paper will determine the factors influencing Gen Z’s attitude towards social media advertisement. The study is descriptive-causal, and to determine the 297 respondents as samples, the stratified sampling technique was used. The findings revealed that perceived usefulness and reliability have a positive effect on Gen Z’s attitude towards social media ads. Word-of-mouth is found to be an insignificant factor. Marketers should consider these results to receive a favorable response in online advertisements.
Keywords: Gen Z; social media attitude; perceived usefulness; reliability; word-of-mouth